REVITALISASI TARI TIMANG BANJAR DI KERATON KADRIYAH KOTA PONTIANAK KALIMANTAN BARAT - Kuantani, Irma Maira; Ismunandar, Ismunandar; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research is the loss of Timang Banjar Dance in Kadriyah Palace. The purpose of this research is to revitalize Timang Banjar Dance in Kadriyah Palace, Pontianak, West Kalimantan so it could exist in the society around Kadriyah Palace. Specifically, this research focuses on how does the process, the form and the result of revitalization of Timang Banjar Dancein Kadriyah Palace, Pontianak West Kalimantan. Method used in this research is descriptive with qualitative method and sociological approach. Data used in this method are the result of interview, observation, documentation and daily note about Timang Banjar Dance. The result of this research is an effort in revitalizing Timang Banjar Dance such as helding a meeting with the interviewees and also the dancer and the musician of this dance in Kadriyah Palace, Pontianak; Dancing Timang Banjar Dance; Evaluating the form of the dance; Represent the Dance by doing workshop, using backsound, properties, and costumes of Timang Banjar Dance. Keywords: Revitalizing, Timang Banjar Dance, Pontianak